2009
DOI: 10.1016/j.jtcvs.2008.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic repair for congenitally corrected transposition of the great arteries

Abstract: The occurrence of left ventricular dysfunction indicate that anatomic repair in the arterial switch group is still fraught with imperfections. The Rastelli group required conduit revisions but has otherwise performed well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 22 publications
(45 reference statements)
2
43
1
Order By: Relevance
“…In patients who require complex biventricular repair or not candidates for biventricular repair, it has been reported that Fontan operation had more successful results (18,24) . Another treatment option for this type of patients is one-and-one half ventricle repair between Fontan circulation and classic conventional physiological surgical repair (25) .…”
Section: Dıscussıonmentioning
confidence: 99%
“…In patients who require complex biventricular repair or not candidates for biventricular repair, it has been reported that Fontan operation had more successful results (18,24) . Another treatment option for this type of patients is one-and-one half ventricle repair between Fontan circulation and classic conventional physiological surgical repair (25) .…”
Section: Dıscussıonmentioning
confidence: 99%
“…20,21 The heart is displaced into the left pleural cavity for adequate atrial exposure and venous cannulation should be direct and extrapericardial. Pericardial/prosthetic patch is used to augment the first and second layers.…”
Section: Atrial Switch Operation In Cctgasmentioning
confidence: 99%
“…Sharma et al (23) reported on double switch operation or congenitally corrected TGA in 68 patients. Group 1 comprised 31 patients at a mean age of 94 months who underwent a combined Rastelli and atrial switch operation.…”
Section: Tgamentioning
confidence: 99%